Economic evaluation of systems intercropping food crops with leguminous cover crops in the derived savanna of Nigeria - Manyong, Victor M.; Tian, G.; Makinde, K.; Kolawole, G.O. (2000)
Simultaneous intercropping is a crop-management strategy that is applied by the majority of small-scale farmers in the derived savanna of West Africa. Developing improved systems that are close to farmers' practices is likely to lead toadoption. This paper report economic results from a 2year on-station evaluation of four systems (sole maize, maize + Mucuna, maize + Pueraria, and maize + Pueraria + Mucuna in the first year, each rotated with maize + cassava in the second year) in which food crops were simultaneously planted with leguminous cover crops with and without fertilizer at Ibadan, Nigeria. Systems with Pueraria and those with Pueraria/Mucuna were more profitable than the others and seemed to be promising technologies for simultaneous intercropping of food crops and cover crops for the derived savanna of West Africa. However, these systems were associated with variability in t5he economic returns that need to be taken into consideration when targeting improved systems to farmers. Improved systems that integrate leguminous cover crops with fertilizer application were technically and economically superior to those without fertilizer. This is an indication that combining cover crops with inorganic fertilizer is an efficient strategy to address the issue of low productivity in West African agriculture.